DISTINGUISHING TRUE HYPERTENSION FROM WHITE COAT HYPERTENSION IN PREGNANT JORDANIAN WOMEN. - AMAL K. SULEIMAN; SALWA S. ABOGALAMBOU (International Journal of Pharma and Bio Sciences, 2014)
The aim of the present study was to identify the practices for using ambulatory blood pressure monitoring to diagnose hypertension and white coat hypertension in pregnant women in Jordan. The study included all obstetricians (Jordanian Medical Association Members) who accepted to be emailed a structured, pre-validated piloted questionnaire. The questionnaire included 4 parts: characteristics of obstetricians, methods for blood pressure assessment responses, diagnosis and management of WCH in pregnancy responses, as well as open-ended questions enquired about barriers faced against the use of self or ambulatory BP monitoring. Data collection took place between May and October 2013. A coding frame for each response in the questionnaire was made and data were entered in Microsoft Excel Software, checked for accuracy then loaded in SPSS (version 18). Response rate was 79.0 %. Out of all obstetricians: (91.4%) reported that they “almost always” or “often” attempt to differentiate WCH from true hypertension in pregnancy, (81.7%) considered Self BP monitoring methods for WCH from true HTN, not sure about the validity and accuracy of home BP devices was the most frequently cited response about barriers to the use of self BP monitoring. Obstetrical in Amman are aware that WCH is an issue among pregnant women. While ABPM is chosen in a minority of cases, as well as strong preference to use self BP monitoring for further BP evaluation.